Study on Layout Design of Curve Tension Constraint and Tension Characteristic of Multi Axis Silent Chain System - Fan Chengyan; Xu Shuxin; Wang Hongjun; Xing Jianheng (Jixie chuandong)
The curve tension is one of the common constraints of automotive engine timing chain system,and its layout design is directly related to the vibration characteristics,noise characteristics and smooth characteristics of the timing chain system. Through an engine timing chain system design as an example,the characteristics of the chain tension of the three axis system are described,and a quantitative description of the tension of the loose side and tension of the tension device are carried out. By using the cylinder head anti drag system test bench,the tension force under different rotating speed and the torque of the crankshaft is tested. From this the load cycle characteristics of the timing chain system are obtained. The results show that the dynamic performance is guaranteed based on chain system,tension constraint should be considered to absorb the wear elongation of timing chain,and the tension force of the force direction,but also take into account the timing chain static strength safety margin. The study has an important significance for the application of the chain in the automotive engine,and it also has some reference for the design of the multi axis chain transmission system.